Characterization and antimicrobial analysis of chitosan composite biodegradable films with addition of ginger essential oil - Nur ‘Adilah, Ismail (2010)
Innovative techniques of preserving food safety and structural integrity as well as complete biodegradability must be adopted. This research involves the development process in making the antimicrobial biodegradable film in order to restrain and inhibit the growth of spoilage and pathogenic bacteria that are contaminating food. The main objective of this research is to formulate the best film for food packaging, which has high thermal, antimicrobial and mechanical properties. The films were prepared by casting method. Chitosan were dissolved in 1% v/v acetic acid and yam starch by heat gelatinized, then PEG and ginger essential oil was added to the mix solution. After that, six analyses were tests for those films. The antimicrobial activity was determined by liquid culture test and agar plate test. The results showed that Sample C has highly antimicrobial properties in order to inhibit more Bacillus subtilis and Escherichia coli in liquid culture medium and has greatest clear zone on agar plate. The films morphology structure was observed using scanning electron microscopy (SEM). The results revealed that Sample C more smooth surface and compact structure. Chemical composition of the films was investigated using fourier transform infrared spectroscopy (FTIR) and revealed that starch, chitosan, essential oil and additives presence in the films. The thermal stability characterization using thermal gravimetric analysis (TGA) and differential scanning calorimetric (DSC) showed that Sample C has higher melting point and high heat resistance. In conclusion, Sample C is the best among three samples, prove that the addition of antimicrobial agent such as essential oil will give a better performance in film making.